Digital Health And Telemedicine In Postpartum Care: A Systematic Review Of Their Impact On Maternal Quality Of Life - Aurina Widya Hapsari; Arih Diyaning Intiasari; Dwi Sarwani (Eduvest - Journal of Universal Studies, 2026)
The postpartum period is an important period characterized by various physical, psychological, social, and emotional changes that can affect the quality of life of the mother. Limited access to postpartum health services, especially in vulnerable groups and areas with limited resources, encourages the development of the use of digital health and telemedicine as an alternative to maternal health services. This study aims to identify, analyze, and synthesize scientific evidence regarding the role of digital health and telemedicine in improving the quality of life of postpartum mothers. The research uses the Systematic Literature Review (SLR) method with reference to the PRISMA guidelines. The literature search process was carried out through Google Scholar using the Publish or Perish application with the keywords "digital health" AND "telemedicine" AND "postpartum" AND "quality of life". Of the 200 articles identified, 14 articles met the inclusion criteria and were analyzed qualitatively. The results of the synthesis show four main themes, namely: (1) digital health in supporting the mental health of postpartum mothers, (2) telemedicine in improving access and continuity of postpartum services, (3) mHealth as a means of monitoring and self-management of maternal health, and (4) the contribution of digital health to the quality of life of postpartum mothers. Various forms of digital interventions have been proven to improve early detection of postpartum depression, reduce anxiety, increase self-efficacy, expand access to health services, and support ongoing monitoring of maternal health.